Rabies in a Vaccinated 9-Month-Old German Shepherd Dog, Akure, 2010: A Case Report. (2nd May 2013) - Qasim, A. M.; Obadua, A. A.; Okewole, P. A.; Tekki, I. S.; Omoleye, O. S.
Abstract : After the onset of symptoms, the clinical course of rabies is almost invariably fatal. Rabies has traditionally been associated with dogs more than any other animal, and in parts of the world where domestic animal control and vaccination programs are limited, dogs remain the most important reservoir of the disease. We report a case of canine rabies in a vaccinated 9-month-old German shepherd female dog. The presenting clinical sign was jaw muscle paralysis with a hanging bronze color like tongue without salivation. Following encephalectomy, a rabies positive diagnosis was confirmed by fluorescent antibody technique at the Rabies Laboratory, National Veterinary Research Institute, Vom. The epidemiology of the rabies case is not understood. This case is of public health significance because of the at-risk population including animal health care service provider and animals. The following were recommended, (a) a reinvigorated control measure that includes the awareness program on prevention, responsible dog ownership with dog registration at veterinary hospitals, and registered veterinary clinics by the government and (b) a yearly rabies vaccination campaign that must be improved through the veterinary public health and other health departments collaborating.